Evaluation of the Implementation of the Principle of Justice in Tax Collection on Individual Taxpayers - Shahrazad Elmaniz (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study focuses on evaluating the application of the principle of fairness in the tax collection system for individual taxpayers in Indonesia. As a fundamental foundation, the principle of fairness demands a proportional distribution of the tax burden based on economic capacity or ability to pay. By adopting a normative legal methodology through regulatory and conceptual approaches, this study qualitatively analyzes secondary data. Research findings indicate that normative manifestations of fairness have been integrated through the progressive Income Tax (PPh) tariff scheme and the Non-Taxable Income (PTKP) instrument, which represents the dimensions of vertical and horizontal fairness. However, the effectiveness of its implementation in the field is still hampered by regulatory complexity, minimal taxpayer compliance, and the phenomena of tax avoidance and evasion. Furthermore, weaknesses in the self-assessment system, which relies on taxpayer integrity, require regulatory simplification, strengthened oversight, and greater transparency to create a sustainable tax ecosystem.